The importance of growth factors for the treatment of chronic wounds in the case of diabetic foot ulcers - Buchberger, Barbara (German Medical Science GMS Publishing House, 2010)
INTRODUCTION: Ulcers as a result of diabetes mellitus are a serious problem with an enormous impact on the overall global disease burden due to the increasing prevalence of diabetes. Because of long hospital stays, rehabilitation, often required home care and the use of social services diabetic foot complications are costly. Therapy with growth factors could be an effective and innovative add-on to standard wound care. RESEARCH QUESTIONS: What is the benefit of therapies with growth factors alone or in combination with other technologies in the treatment of diabetic foot ulcer assessed regarding medical, economical, social, ethical and juridical aspects? METHODS: We systematically searched relevant databases limited to English and German language and publications since 1990. Cost values were adjusted to the price level of 2008 and converted into Euro. A review and an assessment of the quality of publications were conducted following approved methodical standards conforming to evidence-based medicine and health economics. RESULTS: We identified 25 studies (14 randomized controlled trials (RCT), nine cost-effectiveness analyses, two meta-analyses). The RCT compared an add-on therapy to standard wound care with standard wound care/placebo alone or extracellular wound matrix: in six studies becaplermin, in two rhEGF, in one bFGF, and in five studies the metabolically active skin grafts Dermagraft and Apligraf. The study duration ranged from twelve to 20 weeks and the study population included between 17 to 382 patients, average 130 patients. The treatment with becaplermin, rhEGF and skin implants Dermagraft and Apligraf showed in eight out of 13 studies an advantage concerning complete wound closure and the time to complete wound healing. Evidence for a benefit of treatment with bFGF could not be found. In four out of 14 studies the proportion of adverse events was 30% per study group with no difference between the treatment groups. The methodological quality of the studies was affected by significant deficiencies. The results showed becaplermin being cost-effective whereas no obvious statement can be made regarding Dermagraft and Apligraf because of diverging cost bases and incremental cost-effectiveness ratios. DISCUSSION: Differences in standard wound care are complicating the comparison of study results. Taking into consideration the small to very small sample sizes and other methodological flaws with high potential of bias, the validity of the results with regard to effectiveness and cost-effectiveness has to be considered limited. The duration of treatment and follow-up examinations is not long enough to assess the sustainability of the intervention and the surveillance of ulcer recurrences or treatment related adverse events like the development of malignancy. CONCLUSIONS: There are indications of an advantage for the add-on therapy with growth factors in diabetic foot ulcers concerning complete wound closure and the time to complete wound healing. Further more studies of high methodological quality with adequate sample sizes and sufficient follow-up periods are necessary also investigating patient-relevant parameters like the health-related quality of life, the acceptance and tolerance of the intervention in addition to clinical outcomes.